A faster capacity scaling algorithm for minimum cost submodular flow - Fleischer, Lisa; Iwata, Satoru; McCormick, S. Thomas (Mathematical programming, 2002)
We describe an O(n4hmin{logU,n2logn}) capacity scaling algorithm for the minimum cost submodular flow problem. Our algorithm modifies and extends the Edmonds-Karp capacity scaling algorithm for minimum cost flow to solve the minimum cost submodular flow problem. The modification entails scaling a relaxation parameter [delta]. Capacities are relaxed by attaching a complete directed graph with uniform arc capacity [delta] in each scaling phase. We then modify a feasible submodular flow by relaxing the submodular constraints, so that complementary slackness is satisfied. This creates discrepancies between the boundary of the flow and the base polyhedron of a relaxed submodular function. To reduce these discrepancies, we use a variant of the successive shortest path algorithm that augments flow along minimum cost paths of residual capacity at least [delta]. The shortest augmenting path subroutine we use is a variant of Dijkstra's algorithm modified to handle exchange capacity arcs efficiently. The result is a weakly polynomial time algorithm whose running time is better than any existing submodular flow algorithm when U is small and C is big. We also show how to use maximum mean cuts to make the algorithm strongly polynomial. The resulting algorithm is the first capacity scaling algorithm to match the current best strongly polynomial bound for submodular flow.